Ultrathin Defective Nanosheet Subunit ZnIn2S4 Hollow Nanoflowers for Efficient Photocatalytic Hydrogen Evolution - Shuoping Ding; Igor Medic; Norbert Steinfeldt; Tianao Dong; Tim Voelzer; Simon Haida; Jabor Rabeah; Juncheng Hu; Jennifer Strunk (Small Structures, 2023)
Constructing hierarchical and ultrathin‐structured metal sulfides is beneficial for achieving high‐efficiency hydrogen evolution catalysts. Herein, ZnIn2S4 (ZIS) hollow nanoflowers (HNFs) composed of ultrathin nanosheets are creatively synthesized via a facile trisodium citrate‐mediated and stirring‐assisted solvothermal method. Experimental results reveal that the synergy effect of ethanol, trisodium citrate, and continuous stirring during solvothermal synthesis process play a significant role in optimizing microstructure as well as physicochemical properties of as‐prepared ZIS samples. Importantly, the fabricated ZIS HNFs with the thinnest nanosheets (2.28 nm) manifest the highest average photocatalytic hydrogen generation rate of 301.5 μmol h−1, which is 2.3 times higher than that of the pristine ZIS microspheres composed of nanoparticles with Pt as the cocatalyst and triethanolamine (TEOA) as the sacrificial agent and outperforms most reported ZnIn2S4‐based materials under similar testing conditions. Moreover, the optimized sample also shows a hydrogen generation rate of 0.53 μmol h−1.in pure water without any cocatalyst. This controllable agitation of the reaction mixture during the hydro/solvothermal synthesis process offers an eco‐friendly and scalable approach for tuning the microstructure of nanomaterials with enhanced performance for various applications.